Variablity, correlation and path analysis in fennel (Foeniculum vulgare Mill.) - SHARMA, PUNEET AGNIHOTRI, S L DASHORA, R K (Journal of Spices and Aromatic Crops, 1997)
Forty eight collections of fennel (Foeniculum vulgare) showed significant variability for days to flowering, plant height, branches per plant, umbels per plant, umbellets per umbel, grains per umbel, 1000 seed weight, yield per plant and yield per plot at Jobner, India. The broad sense heritability was high for 1000 seed weight, umbels per plant and grain yield per plant while genetic advance was· high for umbels per plant, yield per plant and yield per plot. Grain yield per plot was significant and positively associated with yield per plant, grains per umbel and umbels per plant. Branches per plant showed a high positive, direct effect on yield per plot followed by grains per umbel and plant height.